PARADIGMA PEMIKIRAN NURCHOLISH MADJID TENTANG MODERNISASI - Abbas, Pirhat (Media Akademika, 2007)
Modernity in Indonesia inseparable of two matters. first; posess character, and second; cant free of surely contextual situation. Nurcholis Madjid of the a Indonesian reformer figure. he appeared becaused by the two matters, the character of Nurcholis Madjid modernity is a process making radical changes of think system from irrasional to rasional with in secularization contex.